The Role of Immunohistochemical Analysis as a Tool for the Diagnosis, Prognostic Evaluation and Treatment of Prostate Cancer: A Systematic Review of the Literature - Carneiro, Arie; Barbosa, Álan Roger Gomes; Takemura, Lucas Seiti; Kayano, Paulo Priante; Moran, Natasha Kouvaleski Saviano; Chen, Carolina Ko; Wroclawski, Marcelo Langer; Lemos, Gustavo Caserta; Cunha, Isabela Werneck da; Obara, Marcos Takeo; Tobias-Machado, Marcos; Sowalsky, Adam G.; et al. (Frontiers in Oncology, 2018)
Background: Prostate cancer (PCa) is a heterogeneous disease that lends itself towards numerous therapeutic options depending on its risk stratification. One of the greatest challenges in PCa urologic practice is to select patients who should be referred for biopsy and, for those patients who are diagnosed with cancer, to differentiate between patients with indolent disease from those with an unfavourable prognosis and, to determine ideal patient management and avoid unnecessary interventions. Accordingly, there is a growing body of literature reporting immunohistochemical studies with the objective of determining a prostate cancer prognosis. Among the most frequent biomarkers studied are Ki-67, p53, PTEN, MYC and ERG. Based on these findings, we systematically reviewed articles that assessed the role of these main prognostic markers in prostate cancer. Methods: Consistent with PRISMA guidelines, we performed a systematic literature search throughout the Web of Science and PubMed Medline databases. We considered all types of studies evaluating the role of Ki-67, p53, PTEN, MYC and ERG immunohistochemical analysis in prostate cancer until July 2017. Results: We identified 361 articles, 44 of which were summarized in this review. Diagnostically, no single immunohistochemical marker was able to define a tumour as benign or malignant. Prognostically, Ki-67, p53 and MYC were related to the tumour grade given by Gleason score and to the tumour stage (higher levels related to higher tumour grade). Furthermore, Ki-67 was also related to higher PSA levels, shorter disease-free intervals and shorter tumour-specific survival; the latter was also related to p53. The loss of PTEN protein expression showed a higher association with biochemical recurrence and with a worse prognosis, beyond that predicted by the Gleason score and tumour stage. ERG staining also showed a strong association with biochemical recurrence. Conclusion: There are several studies relating immunohistochemical markers with clinical-laboratorial outcomes in prostate cancer, the most frequent being Ki-67, p53, ERG, PTEN and MYC. However, none of these markers have been validated by literary consensus to be routinely applied in medical practice.